2005
DOI: 10.1111/j.0737-1209.2005.220411.x
|View full text |Cite
|
Sign up to set email alerts
|

The Intervention of Outreach: Best Practices

Abstract: Public health nurses (PHNs) use the intervention of outreach to improve health status by locating "at-risk" or "of interest" populations, providing information about health concerns and linking the population to resources to address the health concerns. The purpose of this study was to analyze PHNs' use of the intervention of outreach. Knowledge about best practices can contribute to the ability to successfully implement outreach activities. The descriptive qualitative study involved interviewing 10 Minnesota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…They provided essential data to prepare monthly and quarterly feedback to individual providers and clinics. They documented the consistency and inconsistency of delivery (fidelity) of the SCRIPT methods (Hardin et al, 2005). If prenatal care service providers want to document delivery of SCRIPT methods, Health-Plan Employer Data and Information Set (HEDIS) performance standards and measures, process evaluation methods used in Trials II and III must be included as part of any evaluation of a new tobacco treatment for pregnant women (Windsor, Whiteside, Solomon, et al 2000, Windsor et al, 1993a, 2000a, 2000b, NCQA, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provided essential data to prepare monthly and quarterly feedback to individual providers and clinics. They documented the consistency and inconsistency of delivery (fidelity) of the SCRIPT methods (Hardin et al, 2005). If prenatal care service providers want to document delivery of SCRIPT methods, Health-Plan Employer Data and Information Set (HEDIS) performance standards and measures, process evaluation methods used in Trials II and III must be included as part of any evaluation of a new tobacco treatment for pregnant women (Windsor, Whiteside, Solomon, et al 2000, Windsor et al, 1993a, 2000a, 2000b, NCQA, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A patient lost-to-follow-up (LTF) was counted as a smoker. All forms were transmitted daily by staff at each clinic to the UAB Data Coordinator using the Teleform software (Hardin et al, 2005). …”
Section: Program Evaluation Designmentioning
confidence: 99%
“…The last purpose defined by the NEW LEAP RLC workgroup in designing the AFF was to strengthen C/PH nurse preceptors' and students' familiarity with the PHIs at all levels of nursing practice (individual/family, community, and systems). This need was identified in the literature by Tembreull and Schaffer (2005), who found lack of awareness of the PHI Wheel in practicing C/PH nurses, and Grumbach, Miller, Mertz, and Finnocchio (2004), who noted lack of confidence on the part of public health nurses in their educational preparedness to use the PHIs at the community and systems levels. The use of the PHI Wheel as a model for the AFF provided opportunities for preceptors and students to increase their awareness of and confidence in describing C/PH experiences using the PHI language at all levels of practice.…”
Section: Appraisal Of the Agency Feedback Formmentioning
confidence: 99%
“…However, although extensive outreach research has been conducted in nursing, public health and other fields, reaching an agreement on the clear definition of outreach remains a challenge [8]. Since the inception of the outreach program services for underserved communities several decades ago, the attributes of outreach and the role of the nurse and community team [9,10] has been continuously discussed. A previous study reported that outreach is one of the functions of public health nurses and particularly it is useful for meeting the needs of vulnerable populations, including high-risk groups [11].…”
Section: Introductionmentioning
confidence: 99%